The influencing factors of health–related quality of life of the general population of Iran during the COVID-19 Pandemic - Shirvani Shiri, Maryam; Karami, Hassan; Ameri, Hosein; Akbari Sari, Ali; Tatari, Maryam; Emamgholipour, Sara; Afshari, Somayeh (Frontiers in Medicine, 2023)
COVID-19 is a global health challenge that negatively affects the health-related quality of life (HRQoL) of the general population. The current study aimed to evaluate HRQoL among the Iranian general population and its associated factors during the COVID-19 pandemic. The data were collected using the EuroQol-5 Dimension-3 levels (EQ-5D-3L) and EQ-5D Visual Analog Scale (EQ VAS) questionnaires through an online survey during the COVID-19 pandemic in 2021. Participants were recruited via social media from Fars province. The multiple binary logistic regression model was used to identify factors influencing participants’ HRQoL. Kolmogorov-Smirnov, T-test, ANOVA, and chi-square test were used. All tests were conducted using the Stata 14.2 and SPSS 16 software at a significant level of %5. A total of 1198 participants were involved in this cross-sectional study. The mean age of participants was 33.3 (SD:10.2) and more than half of the participants were women (55.6%). The mean EQ-5D-3L index value and EQ-VAS of the respondents were 0.80 and 77.53, respectively. The maximum score of the EQ- 5D-3L and EQ-VAS in the present study was 1 and 100 respectively. The most frequently reported problems were anxiety/depression (A/D) (53.7%) followed by pain/discomfort (P/D) (44.2%). Logistic regression models showed that the odds of reporting problems on the A/D dimension increased significantly with supplementary insurance, worry about getting COVID-19, hypertension, and asthma by %35 (OR=1.35), %0.02 (OR=1.02), %83 (OR=1.83), and 6.52 times (OR=6.52), respectively. The odds of problems on the A/D dimension were significantly lower among the male gender, housewives+students, and employers by %54 (OR=0.46), %38 (OR=0.62), and %41 (OR=0.59), respectively. Moreover, the odds of reporting a problem on the P/D dimension decreased significantly with higher age groups and worry about getting COVID-19 by %62 (OR=0.38) and %39 (OR=0.61), respectively. The findings of this study could be helpful for policy-making and economic evaluations. A significant percentage of participants (%53.7) experienced psychological problems during the pandemic. Therefore, effective interventions to increase the quality of life of these vulnerable groups in society are essential.